Analysis of Financial Reports in Measuring Financial Performance at Course and Training Institutions (LKP) in Kampung Inggris Pare District Kediri Regency (Case Study on LKP Nowdays English) - Hana, Choirul; Astari, Ita Yoeli; Maryam, Kristianti Nur (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2024)
The company's financial report is a reference for the company in one period. With the financial report, you can find out whether the company has experienced a profit or loss, in addition to being a benchmark for the company to determine the company's performance from a financial perspective. One measuring tool that can be used to measure company performance is ratio analysis. In this case, researchers will conduct research related to financial performance at LKP Nowdays English, which is one of the English language course institutions in Pare District - Kediri Regency. LKP Nowdays English has succeeded in rising from adversity during the Covid-19 pandemic. As we know, during the pandemic, student admissions decreased drastically which meant that LKP had no income at all, but was still able to survive and continue to grow with the increasing number of students accepted into the LKP. The aim of this research is to determine financial performance in terms of Liquidity Ratios and Solvency Ratios using the Time Series Analysis method, namely comparing the performance of financial reports from previous years. The indicator used to calculate the liquidity ratio is the Current Ratio (CR) while the indicator used to calculate the solvency ratio is the Debt To Asset Ratio (DAR). From this research, the results obtained are that the liquidity ratio is not good because it is below the industry average. This is due to the large number of current assets that are in cash and have not been used optimally. The solvency ratio is said to be good because LKP Nowdays English does not have long-term debt. From the results of this research, it can be recommended to LKP Nowdays English to optimize existing cash and not let it sit, while cash can be used to purchase fixed assets, investment, develop facilities and infrastructure, and increase promotions. From the results of the solvency ratio research, the advice that can be given is that you can make permanent investments using long-term debt.